Evaluation of the Effectiveness of CSR Programs for Persons with Disabilities in the Energy Sector at PT XYZ - Priadi, Dini Primasari; Tasmat, Djulianto; Utha, Maria Ariesta; Kurniawati, Kurniawati (Devotion : Journal of Research and Community Service, 2023)
The evaluation of the effectiveness of the Corporate Social Responsibility (CSR) program aimed at people with disabilities in the energy sector has provided an overview of the program implemented by PT XYZ to support people with disabilities. The CSR program included disability workshops in the field of energy and coffee inclusion. The research results indicate that the CSR program, involving people with disabilities, has delivered tangible benefits to the community. These include increased awareness and reduced stigma surrounding people with disabilities, as well as improved employment opportunities and income for people with disabilities. Additionally, the program has had a positive impact on the environment and the broader community. This program has been successful in integrating people with disabilities into the company's value chain, fostering new habits within society, and creating concrete products or actions that are beneficial.